Linking microscale morphologies to localised performance in singlet fission quantum dot photon multiplier thin films. Issue 31 (25th July 2022) - Toolan, Daniel T. W.; Weir, Michael P.; Dowland, Simon; Winkel, Jurjen F.; Willmott, Jon R.; Zhang, Zhilong; Gray, Victor; Xiao, James; Petty, Anthony J.; Anthony, John E.; Greenham, Neil C.; Friend, Richard H.; et al.
Abstract : Hybrid small-molecule/quantum dot films have the potential to reduce thermalization losses in photovoltaics. Here grazing incidence X-ray scattering and IR microscopy, provide direct links between morphologies and photon multiplication performance. Abstract : Hybrid small-molecule/quantum dot films have the potential to reduce thermalization losses in single-junction photovoltaics as photon multiplication devices. Here grazing incidence X-ray scattering, optical microscopy and IR fluorescence microscopy (probing materials at two distinct wavelengths), provide new insight into highly complex morphologies across nm and μm lengthscales to provide direct links between morphologies and photon multiplication performance. Results show that within the small molecule crystallites three different QD morphologies may be identified; (i) large quantum dot aggregates at the crystallite nucleus, (ii) relatively well-dispersed quantum dots and (iii) as aggregated quantum dots "swept" from the growing crystallite and that regions containing aggregate quantum dot features lead to relatively poor photon multiplication performance. These results establish how combinations of scattering and microscopy may be employed to reveal new insights into the structure and function of small molecule:quantum dot blends.